Photovoltaic production management in a hall of residence with high energy consumption - Ara?jo, Ivo (2022)
A hall of residence with low energy performance was subjected to an extensive retrofitting program due to its high energy consumption, to enhance the building?s energy efficiency and reduce its energy costs and greenhouse gas emissions. The retrofitting program included the integration of a solar photovoltaic (PV) system installed on the building?s flat roof, among other factors. Nevertheless, the electricity supply provided by the system during the daytime proved insufficient to cover the building?s energy demand. Based on this, a study was implemented to analyze the contribution of the electricity produced by the solar PV system throughout the year to reduce power consumption under distinct solar radiation conditions, and to define a strategy to optimize renewable energy use by drawing up a set of organizational measures to be implemented to manage the PV solar system energy strategically. The strategic measures are mainly related to selecting the residence tasks with higher energy consumption to fit into higher PV energy production periods. Additionally, it is fundamental to raise the residence?s occupants? education and awareness of energy efficiency, optimize the excess PV energy produced in specific periods by converting it into other energy forms, and install complementary storage systems for surplus production.